Morphological characteristics and phylogenetic analysis reveal Helvellosebacina filicata sp. nov. and Sebacina aciculicola sp. nov. in Sebacinales from southwest China - Jia-Hui Dong; Xin Zhang; Qian-Xin Guan; Fang Wu (MycoKeys)
Morphological characteristics and phylogenetic analyses based on ITS and nLSU sequences reveal two new species of Sebacinaceae from southwest China, viz. Helvellosebacina filicata sp. nov. and Sebacina aciculicola sp. nov. The two species have similar micromorphology characterized by clampless hyphae, hyphidia with simple septa, longitudinally septate, 4-celled, ovoid to subglobose basidia, and broadly ellipsoid to ovoid basidiospores. However, H. filicata is characterized by cartilaginous to gelatinous, white to cream, sometimes semi-transparent basidiomata; basidiospores measuring 8.6–9.9 × 5.8–7.6 μm; and growth on dead ferns. S. aciculicola is characterized by coriaceous, white-to-cream basidiomata; basidiospores measuring 10.2–12.9 × 6.3–8.7 μm; and growth on needles and bark of Pinus. The two new species are described and illustrated in this study.